Genetic variability and character association studies in bread wheat (Triticum aestivum L.) under two different water regimes - Divya Chaudhary*, Swati, Anil Kumar, Basu Sudhakar Reddy and Rohit (Electronic Journal of Plant Breeding, 2023)
The present study was undertaken to estimate the GCV, PCV, heritability, genetic advance, and correlation for yield and its attributes in a set of forty-nine bread wheat genotypes, assessed under irrigated and rainfed conditions. Relatively high GCV, PCV, heritability, and genetic advance were found for TPP, GYP, and BYP in both conditions. It implying that crop improvement can be achieved by selecting these traits and such characters could be transmitted through hybridization to the progeny. In the correlation study, the highest significant positive correlation was observed between GPS and GWS in both environments. The results demonstrated that TPP and BYP are important components for improving grain yield in both irrigated and rainfed conditions.